THE EFFECT OF LOCATION AND FACILITIES SERVICES USER SATISFACTION CONTAINER LOADING AND UNLOADING IN PORT OF INDONESIA IV (Persero) BRANCH MERAUKE - Tarsisius Kana (International Journal of Social Science and Business, 2018)
The Influence of Location and Facilities Against Satisfaction of Container Unloading Service User at PT Pelabuhan Indonesia IV (Persero) Merauke Branch.This study aims to determine how much influence the location and facilities to the satisfaction of service users. Locations have indicators: access, visibility, traffic and facilities have indicators: organizational characteristics and objectives, land availability and space and space requirements, flexibility, aesthetic factors, communities and the environment, construction and operation costs while service user satisfaction has indicators: customer satisfaction , dimensions of customer satisfaction, confirmation of expectations, repurchase interest, willingness to recommend, customer dissatisfaction.The method used in this research is quantitative method by using the technique of processing descriptive data, data collecting technique with interviews, questionnaires and literature study. Sampling technique used incidental sampling. The measurement using likert scale and processed using SPSS version 23 program to calculate the validity and reliability test, calculate hypothesis test that is t test, f test and coefficient of determination. The result of research shows that location and facility variables together have a positive influence on service user satisfaction at PT Pelabuhan Indonesia IV (Persero) Merauke Branch. This can be proven from the result of F count 39.984> 3.11 with significance level 0.000 ≤ 0.05, then Ho is rejected Ha accepted. Itcan be concluded there is a positive and significant relationship between location and facility to the satisfaction of service users of loading and unloading of containers at PT Pelabuhan Indonesia IV (Persero) Merauke Branch.The result of research shows that location and facility variables together have a positive influence on service user satisfaction at PT Pelabuhan Indonesia IV (Persero) Merauke Branch. This can be proven from the result of F count 39.984> 3.11 with significance level 0.000 ≤ 0.05, then Ho is rejected Ha accepted. It can be concluded there is a positive and significant relationship between location and facility to the satisfaction of service users of loading and unloading of containers at PT Pelabuhan Indonesia IV (Persero) Merauke Branch.